Hacia una ética de la responsabilidad: Derrida y el otro “por venir” en Lévinas - Madrid, Raúl (Sapientia, 2008)
The thesis entertained in the paper is that deconstruction contains in itself an ethical attitude, and that such an attitude takes root intrinsically in its openness to the other and in responsibility facing him. On that purpose, the paper primarily intends to elucidate the concept of deconstruction, characterizing it as a reading protocol consisting of two steps: des-sedimentation and reinscription, being this last moment the one which identifies deconstruction as a singular, not universalizable reading. Afterwards, through the notions of “subject” and “otherness of the text” it is shown how the very bases of deconstructive ethics are centred on the concepts of “I” and “other”. Derrida, as it is proved on the paper, takes these concepts from Lévinas’ work. The ethical moment is the openness to the other that occurs through the responsibility involved in conceiving this other unable for appropriation. Such responsibility configures the general-particular ethical aporia, which is thought as the impossible possibility of a general option, which is at the same time a personal, singular decision. In other terms, it indicates the undecidability between the general norm and the concrete decision. This tension is, in due time, the tension between “justice”, “hospitality” and “negotiation”. The aforementioned shows that ethical action (or deconstructive action) has the same structure than différance, always involved in the iteration of significant.